(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sugiana IP, Andiani AAE, Dewi IGAIP, Karang IWGA, As-Syakur AR, Fharmawan IWE. 2022. Spatial distribution of mangrove health index on three genera dominated zones in Benoa Bay, Bali, Indonesia. Biodiversitas 23: 3407-3418. A study of mangrove forest stratification was conducted in Benoa Bay which experienced high coastal development pressures during the last decade. The study aimed to determine mangrove health index distribution (MHI) and forest community structures along three genera-dominated zones which were Sonneratia, Rhizophora and Bruguiera. Random forest method was applied to classify the areas of distributed genera along the bay. Forest structure was assessed with 54 plots. The forest was mainly composed of Rhizophora and Sonneratia-dominated zones in a respective forest area proportion at approximately 51% and 45%. Those zones were dominated by R. mucronata and S. alba with an importance value index (IVI) at 266.35% and 145.57%, respectively. A narrow Bruguiera zone composed of B. gymnorrhiza domination was found in the most landward area, only covering 4% of the mangrove area. Overall accuracy and a kappa coefficient indicated high accuracy of forest classification at 97% and 0.94 respectively. We found that 47.44% of mangrove areas could be classified into the highest healthiness category indicating that the mangrove forest in Benoa Bay is in excellent condition. The Rhizophora zone made a significant contribution to the entire forest state since the excellent category coverage in this zone was approximately 73.80%.